Injury to the tunica media initiates atherogenesis in the presence of hyperlipidemia - Belhoul-Fakir, Hanane; Wu, Jiansha; Yeow, Yen L.; Musk, Gabrielle C.; Kershaw, Helen; Ingley, Evan; Zhao, Bichen Sophie; Reid, Christopher M.; Lagat, Christopher; Evans, Brian; Thompson, Peter L.; Brown, Michael L.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background and aims Fatty streaks initiating the formation of atheromatous plaque appear in the tunica intima. The tunica media is not known to be a nidus for lipid accumulation initiating atherogenesis. We assessed changes to the tunica media in response to a micro-injury produced in the pig aorta. In addition, we assessed human carotid endarterectomy plaques for indication of atheroma initiation in the tunica media. Methods Three healthy landrace female pigs underwent laparotomy to inject autologous blood and create micro-hematomas at 6 sites within the tunica media of the infrarenal abdominal aorta. These pigs were fed a high-fat diet (HFD) for 4–12 weeks. Post-mortem aortas from all pigs, including a control group of healthy pigs, were serially stained to detect lipid deposits, vasa vasora (VV), immune cell infiltration and inflammatory markers, as well as changes to the vascular smooth muscle cell (vSMC) compartment. Moreover, 25 human carotid endarterectomy (CEA) specimens were evaluated for their lipid composition in the tunica media and intima. Results High lipid clusters, VV density, and immune cell infiltrates were consistently observed at 5 out of 6 injection sites under prolonged hyperlipidemia. The hyperlipidemic diet also affected the vSMC compartment in the tunica media adjacent to the tunica adventitia, which correlated with VV invasion and immune cell infiltration. Analysis of human carotid specimens post-CEA indicated that 32% of patients had significantly greater atheroma in the tunica media than in the arterial intima. Conclusion The arterial intima is not the only site for atherosclerosis initiation. We show that injury to the media can trigger atherogenesis.